Development of Efficacy-Enhanced Heart Failure Rehabilitation Patient Education Materials for Health Behavior Change - Wan Juhaini, Paizi@Fauzi; Anwar, Suhaimi; Wan Jumani, Paizi@Fauzi; Tze Yang, Chung (Taylor & Francis, 2023)
Background: Patient education materials (PEMs) are often used in health education programs to empower patients to self-manage their disease for better health outcomes. Heart failure (HF) patients wanted more information about self-management and educational materials that were easy to understand. Programs with self-efficacy as the core component have proven to be effective in improving patients’ self-management. Purpose: To develop practical, efficacy-enhanced, tailored HF rehabilitation PEMs that satisfy our clients to drive long-lasting behavior change and evaluate the materials’ quality (readability, understandability, actionability, and acceptability). Methods: Exploratory mixed methods study involving: i) semi-structured interviews; ii) evaluation of the PEMs; iii) revision and reevaluation of the PEMs; iv) publication. An appointed panel of experts evaluates content accuracy, understandability, and actionability. The Patient Education Material Assessment Tool assesses content understandability and actionability. The content read ability was assessed using Flesch Kincaid Calculator. Clients’ acceptability was assessed using Educational Material Acceptability tool. Results: The newly developed PEMs have good understandability, actionability, readability, and acceptance. Discussion: Patient-centered PEMs have good acceptance and satisfaction among clients. However, the effectiveness of tailored efficacy-enhanced PEMs for behavior changes needs further evaluation. Translation to Health Education Practice: All stakeholders should be included in developing PEMs